Acute diarrhoea due to a Shiga toxin 2e-producing Escherichia coli O8 : H19. (14th June 2017) - Saupe, Angela; Edel, Birgit; Pfister, Wolfgang; Löffler, Bettina; Ehricht, Ralf; Rödel, Jürgen
Abstract : Introduction. Identification of non-O157 Shiga-toxin-producing Escherichia coli (STEC) infections may be underestimated in microbiological diagnosis. Case presentation. A 58-year-old woman developed diarrhoea with watery and subsequently mucous stool. Initial multiplex PCR testing revealed a positive result for stx2 . Culture isolation of a STEC was successful only after repeated inoculation of chromogenic E. coli media. Molecular characterization was performed and identified the isolate as stx 2e -positive STEC of serotype O8 : H19. The strain harboured lpfA, but not eae . Conclusion. This case highlights the usefulness of initial multiplex PCR for diagnosis of non-O157 STEC infection.